Efficacy of low-dose insulin combined with electrolyte in the treatment of pediatric diabetic ketoacidosis and its effect on serum inflammatory factors - Wei, Meili; Feng, Lihe; Zhao, Wei (Cellular and Molecular Biology, 2020)
Diabetic ketoacidosis (DKA) is a very serious disease that can occur in both types of diabetes (type 1 and 2). It is caused by a combination of high blood sugar and low insulin levels, which can cause the body to produce too much ketone. Ketones are toxic to human organs. This research aimed to investigate the clinical efficacy of low-dose insulin combined with electrolyte in the treatment of pediatric DKA and its effect on serum inflammatory factors. For this purpose, a total of 122 children with DKA admitted to our hospital from April 2013 to May 2016 were selected as research objects. They were divided into group A with 60 cases and group B with 62 cases. Group B was treated with supplemental electrolytes, and group A was treated with low-dose insulin based on group B. The serum levels of TNF-Î±, IL-6, and IL-18 were measured by enzyme-linked immunosorbent assay (ELISA) before and after treatment, and the blood sugar, sodium, and potassium levels were measured by an automatic biochemical analyzer. The time when blood sugar reached the standard level when acidosis was corrected and hospitalization time was compared between the two groups. The total effective rate of group A was significantly higher than that of group B (p< 0.05). There was no significant difference in blood glucose, sodium, potassium, TNF-Î±, IL-6, and IL-18 levels between the two groups before treatment. (all p > 0.05). But the blood glucose, sodium and potassium levels in group A were significantly better than those in group B (all p< 0.001). The levels of serum TNF-Î±, IL-6, and IL-18 in group A were significantly lower than those in group B after treatment (all p< 0.001). After treatment, the time when blood sugar reached the standard level when acidosis was corrected and hospitalization time in group A were significantly shorter than those in group B (all p< 0.001). Low-dose insulin combined with electrolyte supplementation is effective in the treatment of DKA in children, which can effectively control blood sugar, sodium, potassium level, and inflammatory factor concentration.